Dendritic cell activation and cytokine response in vaccine breakthrough TBE patients after in vitro stimulation with TBEV - Marušić, Miša; Kopitar, Andreja Nataša; Korva, Miša; Knap, Nataša; Bogovič, Petra; Strle, Franc; Ihan, Alojz; Avšič-Županc, Tatjana (Frontiers in Immunology, 2023)
Tick-borne encephalitis (TBE) is a viral infection of the human central nervous system caused by the TBE virus (TBEV). The most effective protective measure against TBE is vaccination. Despite the highly immunogenic vaccine, cases of vaccine breakthroughs (VBTs) occur. One of the first targets of infection is dendritic cells (DC), which represent a fundamental bridge between innate and adaptive immunity through antigen presentation, costimulation, and cytokine production. Therefore, we investigated the activation and maturation of DCs and cytokine production after in vitro TBEV stimulation of peripheral blood mononuclear cells (PBMCs) obtained from VBT and unvaccinated TBE patients. Our results showed that the expression of HLA-DR and CD86 on DCs, was upregulated to a similar extent in both vaccinated and unvaccinated TBE patients but differed in cytokine production after stimulation with TBEV. PBMCs from patients with VBT TBE responded with lower levels of IFN-α and the proinflammatory cytokines IL-12 (p70) and IL-15 after 24- and 48-hour in vitro stimulation with TBEV, possibly facilitating viral replication and influencing the development of cell-mediated immunity. On the other hand, significantly higher levels of IL-6 in addition to higher TNF-α measured after 6 days of in vitro stimulation of PBMC could support disruption of the blood–brain barrier and promote viral and immune cell influx into the CNS, leading to more severe disease in VBT TBE patients.